Instructions by canon law system (can. 34 § 1–3 CCL) - Dzierżon, Ginter (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The author presents an interpretation of can. 34 § 1–3 CCL concerning instructions. The analyses show that today names of general measures issued by authorities having the executive power present a big conceptual chaos. The author has proven that the facts indicate that the intention of the legislature in the work of codification aiming to standardize the names misfired. In his opinion, the norm included in canon. 34 CCL remains only a written record because a definition of instructions codified in canon. 34 § 1 of the CCL is in practice the only point of reference which allows classifying general application acts issued by the executive power.